Destination of New Guinea Coastal Undercurrent in the western tropical Pacific: Variability and linkages - Azminuddin, Fuad; Jang, Chan Joo; Jeon, Dongchull (Frontiers in Marine Science, 2022)
The New Guinea Coastal Undercurrent (NGCUC) is considered a bottleneck in the western tropical Pacific (WTP), carrying upper-to-intermediate waters from the south to the northwestern Pacific, thereby playing a fundamen tal role in the interhemispheric water mass exchange. However, how the NGCUC links to the circulation in the WTP was insufficiently studied. This work explores the destination of NGCUC waters, its spatiotemporal changes, and possible physical processes linked with the downstream NGCUC using ocean reanalysis for 22 years (1994 – 2015). Lagrangian particle tracking discloses eight major destinations of the NGCUC: The Equatorial Undercurrent (EUC, 35.26%), the North Equatorial Countercurrent (NECC, 12.3%), the North (13.33%) and South (8.85%) Subsurface Countercurrents, the Equatorial Deep Jet (11.49%), the Mindanao Undercurrent (13.24%), and the Indonesian (3.47%) and Halmahera (0.86%) Throughflows. The NGCUC waters are distributed mainly to the east (81.65%) and their dissemination varies markedly with depth. These destinations exhibit significant variations on seasonal and interannual time scales. The NGCUC strengthens (weakens) during summer (winter) and more NGCUC waters are distributed westward and northeastward (eastward). Interannually, the distribution of the NGCUC water is influenced by El Niño-Southern Oscillation, in which most of its eastward-distributed waters shift northward (equatorward) in El Niño (La Niña) phase joining the strengthened NECC (EUC). Changes in the NGCUC water destination can transform the water mass properties in the WTP. The findings of this study also emphasize the fundamental role of eddies in trapping and redistributing the NGCUC waters and linking the currents in the WTP.